Malpractice Dispute Resolution Conducted By Notary (Supreme Court Ruling Study Number: 2377 K/Pdt/2016) - Indra Kurniawan (Authentica, 2020)
A notary is a public official who is authorized by the state to make an authentic deed, the authority of this notary has been regulated in the Act of Notary (UUJN) and the Code of Ethics for Notary. Notary in making authentic deeds, solving challenges that lead to malpractice. The data used are secondary data and primary data as a complement to secondary data. The method used in this study is a method that discusses normative juridical. The research results obtained are 2 (two) notaries acceptable to malpractice, namely forms of denial or deviation and ability of the duties and responsibilities of the notary, either because of problems or negligence that can be justified. Accountability of the notary in the case of malpractice actions can be carried out on the basis of a moral law that will be borne by the notary if they carry out malpractice. The dispute resolution process carried out by a notary can be done through the Notary Supervisory Board, but cannot discuss the agreements that can be made in the Court.Keywords: Notary Liability, Malpractice, Dispute Resolution